2013
DOI: 10.1088/0741-3335/55/7/074016
|View full text |Cite
|
Sign up to set email alerts
|

Global gyrokinetic simulations of TEM microturbulence

Abstract: Global gyrokinetic simulations of electrostatic temperature-gradient-driven trapped-electron-mode (TEM) turbulence using the δf particle-in-cell code ORB5 are presented. The electron response is either fully kinetic or hybrid, i.e. considering kinetic trapped and adiabatic passing electrons. A linear benchmark in the TEM regime against the Eulerian-based code GENE is presented. Two different methods for controlling the numerical noise, based, respectively, on a Krook operator and a so-called coarse-graining ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…25 Several studies have shown that those parameters can present TEM modes well at wavelength, k θ ρ i 1. 25,26 ETG modes can also be linearly unstable for these parameters at shorter wavelengths, with poloidal wave number k θ ρ i 1. 26 Although their existence can influence the electron heat flux significantly, their impact on α particle transport is expected to be negligible due to the following reasons.…”
Section: Results From Linear Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Several studies have shown that those parameters can present TEM modes well at wavelength, k θ ρ i 1. 25,26 ETG modes can also be linearly unstable for these parameters at shorter wavelengths, with poloidal wave number k θ ρ i 1. 26 Although their existence can influence the electron heat flux significantly, their impact on α particle transport is expected to be negligible due to the following reasons.…”
Section: Results From Linear Simulationsmentioning
confidence: 99%
“…25,26 ETG modes can also be linearly unstable for these parameters at shorter wavelengths, with poloidal wave number k θ ρ i 1. 26 Although their existence can influence the electron heat flux significantly, their impact on α particle transport is expected to be negligible due to the following reasons. With large spatial scale separation between α particle orbit and ETG wavelength, even stronger orbitaveraging and the frequency detuning 10,11 would occur compared to those for TEM.…”
Section: Results From Linear Simulationsmentioning
confidence: 99%
“…Moreover, trapped electron modes (TEM) could be destabilized, in particular once ITGs are stabilized by ZF. First nonlinear TEM results in circular plasmas at low 1/ρ * [30,31] indicate that TEMs are less effectively suppressed by ZF shearing than ITG. Second, ion-ion collisions are known to damp the ZF, resulting in nonzero turbulent transport in the 'Dimits shift' region [20].…”
Section: Resultsmentioning
confidence: 99%
“…2004, 2006; Vernay et al. 2013). The NEMORB gyrokinetic model, in the electrostatic limit, is based on the gyrokinetic Vlasov–Poisson system of equations described in the previous section: where is a collision operator and is a heat source term.…”
Section: Resultsmentioning
confidence: 99%
“…The linearised field equations, the polarisation equation and the parallel Ampère's law are discretised using B-splines. The code is based on straight-field-line coordinates and includes collision operators (Vernay et al 2010), shaped MHD equilibria and a hybrid model for the trapped electrons (Bottino et al 2004(Bottino et al , 2006Vernay et al 2013). The NEMORB gyrokinetic model, in the electrostatic limit, is based on the gyrokinetic Vlasov-Poisson system of equations described in the previous section:…”
Section: Resultsmentioning
confidence: 99%